Low concentrations of local honey modulate ETA expression, and quorum sensing related virulence in drug-resistant Pseudomonas aeruginosa recovered from infected burn wounds - Akhter A Ahmed; Fraidoon A Salih (Iranian Journal of Basic Medical Sciences, 2019)
Objective(s): Honey’s ability to kill microorganisms and even eradication of chronic infections with drug-resistant pathogens has been documented by numerous studies. The present study is focused on the action of honey in its sub-inhibitory levels to impact on the pathogens coordinated behaviors rather than killing them. Materials and Methods: The impact of local honey on the quorum sensing related virulence of multidrug resistant Pseudomonas aeruginosa burn isolates was investigated by detection its effect on the virulence, biofilm formation and expression of quorum sensing related and exotoxin A genes.Results: Experiments to characterise and quantify the impact of honey on the P. aeruginosa quorum sensing networks showed that the expression of exotoxin A ( ETA), las and rhl glucons reduced by low concentrations of honey including the associated virulence factors. Conclusion: Our results indicated that honey fights infections either by its bactericidal components which vigorously kill cells or by weakening bacterial coordination and virulence through interruption of quorum sensing system.